Mighty Thor. 5, The death of the mighty Thor - Aaron, Jason (Mighty thor, 2018)
The final judgement comes as the mangog arrives. The War Thor meets the beast head-on, but even the bloothirst of this ultimate hammer-wielder may pale in comparions to the Mangog's might. The battle rages as Jane Foster's cancer takes a turn for the worse, and she might not have to wait for the final judgment at all. The clock is ticking, the war of the Realms is spreading and Mjolnir cannot save her this time. Can Doctor Strange and the Falcon help avert disaster? The tragic and heroic story of Jane Foster finally reaches its heartrending zenith!